Morphological diversity, cultivar groups and possible descent in the cultivated yams (Dioscorea cayenensis/D. rotundata) complex in Benin Republic - Dansi, A.; Mignouna, Hodeba D.; Zoundjihékpon, J.; Sangare, A.; Asiedu, Robert; Quin, F.M. (1999)
A better knowledge of traditional cultivars is a prerequisite to overcoming the various constraints of yam production in Benin. Using IPGRI's descriptors, 560 accessions of cultivated yams (D. cayenensis Lam./D. rotundata Poir. complex) collected throughout Benin, were characterised. Ninety morphotypes were identified and further classified into 26 cultivar groups based on their morphological similarities. An identification key is proposed for the cultivar groups. The geographical distribution of cultivar groups is also presented and two centres of diversity are identified. A comparative study between the cultivated forms and their wild relatives (D. abyssinica Hochst., D. praehensilis Benth and D. burkilliana Miège) has allowed us to establish linkages between the identified morphotypes and wild species and to postulate some hypotheses which will be further tested using isozyme and DNA markers. The flowering and the fruiting capacity of the morphotypes as well as their adaptability (based on tuber morphology) to mechanical harvesting are also discussed. Some collections in Nigeria (IITA, Ibadan) and Togo containing cultivars from many West African countries were inspected to verify the geographical distribution of Beninese cultivars.